AGENDA SETTING PORTAL MEDIA ONLINE BALI.TRIBUNNEWS.COM DALAM PEMBERITAAN RANCANGAN UNDANG-UNDANG PERMUSIKAN - Berdianti, Dian; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2020)
AB S TRACT   The problem of this research is about the agenda setting of bali.tribunnews.com in reporting on the draft law about music. This study aims to provide information about the process of media agenda settings that have an impact on the formation of public opinion. This research is a mixed methods research with sequential mixed methods strategy. The research design used for the qualitative phase of this study is Robert N. Entman's framing analysis. The results of the research show that (1)Draft Laws are widely opposed by musicians because there are articles that are unclear;(2)This Draft Law is deemed not to be made without a strong and unimportant basis;(3)The draft of this Law is made unlike the agreement or the results of a music conference;(4)Musicians feel that this Draft Act curbs their freedom of expression and discriminates them.   K eywords: A g enda Setting, Media Online